1992
DOI: 10.1111/j.1432-1033.1992.tb17231.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of vanillyl‐alcohol oxidase from Penicillium simplicissimum

Abstract: Vanillyl-alcohol oxidase was purified 32-fold from Penicillium simplicissimum, grown on veratryl alcohol as its sole source of carbon and energy. SDSjPAGE of the purified enzyme reveals a single fluorescent band of 65 kDa. Gel filtration and sedimentation-velocity experiments indicate that the purified enzyme exists in solution as an octamer, containing 1 molecule flavin/subunit. The covalently bound prosthetic group of the enzyme was identified as 8cr-(N3-histidyl)-FAD from pH-dependent fluorescence quenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 24 publications
(25 reference statements)
9
109
1
Order By: Relevance
“…The concentration of VAO was determined spectrophotometrically using a molar absorption coefficient E439 = 12.5 mM _1 cm -1 for protein-bound FAD [1]. VAO substrates and competitive inhibitors have been described elsewhere [2].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of VAO was determined spectrophotometrically using a molar absorption coefficient E439 = 12.5 mM _1 cm -1 for protein-bound FAD [1]. VAO substrates and competitive inhibitors have been described elsewhere [2].…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme is a homooctamer of 0.5 MDa with each subunit containing Soc-iTV^-histidyrj-FAD as a covalently bound prosthetic group [1]. Based on the production of 4-hydroxycinnamyl alcohols from 4-allylphenols we have proposed that the reaction mechanism of VAO involves the formation of a />-quinone methide product intermediate [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified VAO mutants T457E, D170A͞T457E, and D170S͞T457E were bright yellow, and their near UV absorption properties were virtually identical to wildtype enzyme (29). Fluorescence analysis of unstained SDS gels showed that the mutant enzymes were as fluorescent as wildtype VAO.…”
Section: Resultsmentioning
confidence: 87%
“…Fluorescence analysis of unstained SDS gels showed that the mutant enzymes were as fluorescent as wildtype VAO. This fluorescence behavior, and the fact that the mutants did not release any flavin upon trichloroacetic acid treatment (29), indicated that all flavin was covalently bound. Moreover, analytical gel filtration revealed that the mutants were mainly octameric, with only a small fraction in the dimeric form.…”
Section: Resultsmentioning
confidence: 92%